2015
DOI: 10.1080/15532739.2015.1075930
|View full text |Cite
|
Sign up to set email alerts
|

Gender Affirmation and Body Modification Among Transgender Persons in Bogotá, Colombia

Abstract: This paper examined structural, social, and personal characteristics that shape the processes of gender affirmation and body modification among transgender persons (assigned male at birth) in Bogotá, Colombia. Qualitative data from life-history interviews (N=14) and a focus group (N=11) explored research questions concerning the ways in which the internal psychological and external contextual processes influence individuals' decisions and behaviors concerning hormonal treatment, injections, or surgery. Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
2
16
0
1
Order By: Relevance
“…In many countries and geographic contexts, medical gender affirmation is excluded from mainstream delivery or primary care services for transgender people and thereby relegated outside of the health care system. Lack of knowledgeable health care providers combined with transphobia and stigma in health care delivery systems may lead transgender people to procure gender-affirmative medical care through informal peer or community networks, 22 24 which may increase risk of health complications (eg, lack of routine monitoring of hormone levels, using higher than recommended dosages of hormones). Inability to legally affirm gender through legal documents (eg, government-issued identification) that match one's gender identity can be a barrier to accessing and receiving health care services, particularly within socialized government supported and sponsored health care systems.…”
Section: Gender Affirmation As a Key Social Determinant Of Trans Healmentioning
confidence: 99%
“…In many countries and geographic contexts, medical gender affirmation is excluded from mainstream delivery or primary care services for transgender people and thereby relegated outside of the health care system. Lack of knowledgeable health care providers combined with transphobia and stigma in health care delivery systems may lead transgender people to procure gender-affirmative medical care through informal peer or community networks, 22 24 which may increase risk of health complications (eg, lack of routine monitoring of hormone levels, using higher than recommended dosages of hormones). Inability to legally affirm gender through legal documents (eg, government-issued identification) that match one's gender identity can be a barrier to accessing and receiving health care services, particularly within socialized government supported and sponsored health care systems.…”
Section: Gender Affirmation As a Key Social Determinant Of Trans Healmentioning
confidence: 99%
“…One definition may include all those modifications that are non‐medical and voluntary (Keagy, ), often limiting the sample to piercings and tattoos (Martin & Cairns, ) or just piercings (Swami et al, ). Another includes all those voluntary body projects, including those undertaken in medical contexts, such as gender reassignment (Aguayo‐Romero, Reisen, Zea, Bianchi, & Poppen, ), weight loss/gain, or cosmetic surgery (Karupiah, ). A more broad definition is “procedures to achieve permanent alterations of the human body” (Stirn et al, : 359).…”
Section: Definitional Dilemmasmentioning
confidence: 99%
“…This conceptualization separates many different kinds of body projects from body modification. For example, there are a number of body projects that could be placed under the name of modification, including clothing, hair styling, cosmetic surgery (Gimlin, 2010), gender reassignment surgery (Aguayo-Romero et al, 2015), labia elongation (Koster & Price, 2008), body building (Chananie-Hill, McGrath, & Stoll, 2012), and even intentional weight gaining (Monaghan, 2005). However, each of these does not fulfill as least one of the four components described in the conceptualization.…”
Section: Cultural Boundaries and Status Group Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, meaningful social and romantic relationships may provide transwomen a resource of social support and GA. 14 For example, a qualitative study of transgender GA by Aguayo-Romero et al found that social peers, including sexual and romantic partners of transwomen, constitute an important source of encouragement and gender identity acceptance. 15 However, as Nuttbrock et al have highlighted, GA through sexual relationships, including commercial sexual relationships (i.e., sex work), may have mental health benefits but may need to be balanced by potential health risks, including HIV risk. 14 Further, Bockting et al have suggested a gender affirming benefit for transwomen engaging in receptive anal sex.…”
Section: Introductionmentioning
confidence: 99%